Kekerasan Berbasis Gender Di Media Sosial - Jihan Risya Cahyani Prameswari; Deassy Jacomina Anthoneta Hehanussa; Yonna Beatrix Salamor (PAMALI: Pattimura Magister Law Review, 2021)
Introduction: Gender based violence in social media has increased. The term of gender based violence can be found on the result of Convention on the Elimination of all Forms of Discrimination Against Women, however there are still not any proper effort to overcome it yet.Purposes of the Research: Knowing and analyzing gender-based violence on social media..Methods of the Research: This study uses a normative juridical method with legal materials used in the study are primary, secondary and tertiary with the use of literature study techniques in the form of international legal regulations, scientific papers and literature.Results of the Research: There are several forms and types of gender based violence in social media like cyber grooming, hacking, infringement of privacy, malicious distribution, revenge porn, impersonation, defamation, and online recruitment. Hence as the way to overcome it, the efforts that can be used is by penal and non-penal efforts. The penal efforts are the implementation of the integrated criminal justice system with gender justice and the regulatory reform through a bill to accommodate the criminal act of gender based violence. Meanwhile the non-penal efforts are by increasing the awareness and knowledge through the campaign movement against gender based violence in social media and providing the complaint and report service accesses (hotline) that are easy to be accessed and fast to respond.